Industrial tomographic gamma scan for demister evaluation. (July 2021) - Haraguchi, Marcio I.; Kim, Hae Yong
Highlights: The new NDT industrial 2-D gamma scan was applied to a large drum with demisters. It reconstructs the internal density of the equipment in a rectangular domain. Instruments are positioned only laterally to the equipment. Electronic collimation for gamma scan allows obtaining collimated data. Prior information is essential to reconstruct the low density demisters. Abstract: The industrial tomographic 2-D gamma scan is an innovative non-destructive nuclear test designed to troubleshoot problems with process equipment, such as distillation columns and reactors. Due to physical restrictions, normally the gamma ray source and detector can only be positioned laterally to the equipment. The 2-D gamma scan is able to reconstruct the interior of the equipment even under this restriction, generating rectangular 2-D axial density profiles of equipment. To obtain clear reconstructions, it is necessary to collimate the detector, discarding the divergent incoming rays. It is not possible to use physical collimation in an industrial environment, as it is impossible to point the detector precisely in the direction of the gamma-ray emitter. In this article, we describe a technique we call "electronic collimation for gamma scan" that allows obtaining collimated data without physical collimation. We use 2-D gamma scan to evaluate a huge dilution steam drum in a large petrochemical plant to investigate possible problems with three demister pads. The low density of the demisters when compared to the vessel and surroundings makes it difficult to generate a reconstructed image where demisters are clearly visible. We describe how we overcome these difficulties using information known a priori about the equipment. We also ran simulations to show the superiority of 2-D gamma scan over conventional scan. These simulations also showed that, if there were defects in the demisters, we would observe them in the reconstructed images. We conclude that electronic collimation and prior information are essential for evaluating properly equipment with challenging layouts and low density parts.